Hybrid/Chimera Drugs - Part 1 - Drug Hybrids Affecting Diseases of the Central Nervous System - Nudelman, Abraham (Current Medicinal Chemistry, 2025)
This review, focused on hybrid drugs, is the third in a series of reviews, where the first two reviews dealt with a) dimeric drugs, b) mutual prodrugs – codrugs. The compounds designated as hybrids are comprised of two (and sometimes three) biologically active entities, linked by metabolically stable bridges. In some cases, one of the two components of the hybrids serves as a carrier for the second component, and most frequently, the components elicit their individual biological properties, which are commonly synergistic or complementary. Due to the very large number of publications dealing with hybrid drugs, the present review is restricted to hybrids acting in the central nervous system. Future reviews will cover fields such as antimicrobial, anticancer, and antiviral hybrids, and cardiovascular active hybrids. The selected articles reviewed herein were published between the years 2000-2022 with partial coverage of the year 2023.
Keywords: synergy